Critical Communication Theory and Social Issue Representation in Taxi Driver II - Aminiatyn Niswah, Farah; Dwi Ayuni, Risa; Agus Humaidi, Muhammad (Arbain Publishing, 2026)
Drama, as a form of mass communication media, has the capacity to disseminate information, convey ideas, and influence audience behavior. Taxi Driver, a drama centered on the overarching themes of revenge and the pursuit of justice, presents representations of social issues through the lens of critical communication theory. This study employs critical discourse analysis based on the models developed by Norman Fairclough and Teun A. Van Dijk to examine the representation of social issues in Taxi Driver II, to analyze how the characters embody principles of critical communication theory, and to identify the impacts and messages conveyed to viewers. The findings of the critical discourse analysis using these two models demonstrate that the drama represents a wide range of social issues, including legal injustice, human trafficking, fraud targeting the elderly, child exploitation, cult-related fraud, medical malpractice, and illegal business operations. These social issues are articulated through scenes, character actions, dialogues, metaphors, and other narrative elements. The character Kim Do Gi emerges as an icon of the struggle for justice and exemplifies the application of critical communication theory in challenging domination and combating injustice. The narrative and characterization collectively convey messages that encourage viewers to become more attentive to their social surroundings and to cultivate a commitment to advocating for justice within society.